Mutation at the tomato EXCESSIVE NUMBER OF FLORAL ORGANS (ENO) locus impairs floral meristem development, thus promoting an increased number of floral organs and fruit size. (March 2015) - Fernández-Lozano, Antonia; Yuste-Lisbona, Fernando J.; Pérez-Martín, Fernando; Pineda, Benito; Moreno, Vicente; Lozano, Rafael; Angosto, Trinidad
Highlights: eno is a novel mutation affecting floral meristem and fruit development of tomato. eno mutation impairs the temporal expression pattern of SlWUS and IMA genes. ENO gene function is required to control organ number during flower development. Abstract: A novel tomato ( Solanum lycopersicum L.) mutant affected in reproductive development, excessive number of floral organs ( eno ), is described in this study. The eno plants yielded flowers with a higher number of floral organs in the three innermost floral whorls and larger fruits than those found in wild-type plants. Scanning-electron microscopy study indicated that the rise in floral organ number and fruit size correlates with an increased size of floral meristem at early developmental stages. It has been reported that mutation at the FASCIATED ( FAS ) gene causes the development of flowers with supernumerary organs; however, complementation test and genetic mapping analyses proved that ENO is not an allele of the FAS locus. Furthermore, expression of WUSCHEL ( SlWUS ) and INHIBITOR OF MERISTEM ACTIVITY ( IMA ), the two main regulators of floral meristem activity in tomato, is altered in eno but not in fas flowers indicating that ENO could exert its function in the floral meristem independently of FAS . Interestingly, the eno mutation delayed the expression of IMA leading to a prolonged expression of SlWUS, which would explain the greater size of floral meristem. Taken together, results showed that ENO plays a significant role in the genetic pathway regulating tomato floral meristem development.